2019
DOI: 10.1080/15388220.2019.1636383
|View full text |Cite
|
Sign up to set email alerts
|

Moral Disengagement and School Bullying Perpetration in Middle Childhood: A Short-Term Longitudinal Study in Sweden

Abstract: The aim of the current study was to longitudinally investigate the bi-directional relationship between moral disengagement and bullying perpetration in a sample of 1,354 students from 108 elementary classes in 69 public schools. Students participated in the study both at Time 1 (fourth grade) and around one year later at Time 2 (fifth grade). Structural equation model analyses showed that bullying perpetration at Time 1 predicted moral disengagement at Time 2, when controlling for moral disengagement stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 42 publications
(69 reference statements)
4
30
0
1
Order By: Relevance
“…Previous studies, taking the mechanism of moral disengagement as a one-dimensional construct, have shown that higher scores in perpetration in bullying predict higher scores in moral disengagement (Obermann, 2013;Thornberg et al, 2019). However, to date, no longitudinal studies have explored the possible influence of aggressive behavior within bullying on the different mechanisms of moral disengagement.…”
Section: Aggression In Bullying and Moral Disengagementmentioning
confidence: 99%
“…Previous studies, taking the mechanism of moral disengagement as a one-dimensional construct, have shown that higher scores in perpetration in bullying predict higher scores in moral disengagement (Obermann, 2013;Thornberg et al, 2019). However, to date, no longitudinal studies have explored the possible influence of aggressive behavior within bullying on the different mechanisms of moral disengagement.…”
Section: Aggression In Bullying and Moral Disengagementmentioning
confidence: 99%
“…Has ascertained whether an ontology could be applied to provide information about the quality of art education in a variety of different contexts [6]. Suggests that educators, school staff, and professionals should consider interventions that discuss morals when learning with students [7]. Intervention must be built on the positive relationship of both educators and students with the aim of targeting self-control and peer conflict [8].…”
Section: Background: Arts Policy At Primary Schoolmentioning
confidence: 99%
“…Then in laras slendro there are three pathets, namely the pathet sanga, pathet nem, and pathet manyura. Whereas for laras pelog tunings there are seven (7) scales or notes, including ji (1), ro (2), lu (3), pat (4), mo (5), nem (6), and pi (7). Then in laras pelog there are 3 pathets, namely pathet limo, pathet nem, and pathet barang.…”
Section: Karawitan As Traditional-musical Arts Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moral disengagement juga digunakan di penelitian untuk melihat kecenderungan perilaku bullying di sekolah. Penelitian ini memang dijelaskan bahwa individu menggunakan moral disengagement untuk membenarkan perbuatan bullying yang mereka lakukan (Thornberg, Wänström, Pozzoli, & Hong, 2019). Dengan demikian, moral disengagement ini secara konsisten dari awal kehadirannya hingga saat ini menunjukkan faktor yang berhubungan dengan tindakan pelanggaran moral.…”
Section: Pendahuluanunclassified